Digital Fiqh: Contextualizing Digital Media (The Law of AI and Big Data) - R, Rahmatullah; Haddade, Abdul Wahid; P, Patimah (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The development of digital technology has given rise to various new phenomena in the social, economic, and religious lives of Muslims. This condition calls for a methodological renewal in understanding Islamic law that is adaptive to changing times. This article discusses the reconstruction of digital fiqh as an effort to apply the principle of ta?b?q al-a?k?m ‘al? al-naw?zil (the application of legal rulings to new issues), grounded in naql? (textual) evidence, ‘aql? (rational) reasoning, and ijtih?diyyah legal maxims. The study finds that the conceptual foundation of digital fiqh encompasses the values of trustworthiness (am?nah), responsibility, and the prohibition of causing harm to others, as emphasized in the Qur’an and the Sunnah. The contextualization of digital fiqh is divided into four main areas: fiqh al-ma‘l?m?t (fiqh of information), fiqh al-mu‘?mal?t al-raqmiyyah (fiqh of digital transactions), fiqh al-da‘wah al-raqmiyyah (fiqh of digital da‘wah), and fiqh al-akhl?q al-raqmiyyah (fiqh of digital ethics). U??l? and maq??id? approaches are employed to ensure that the principles of ?if? al-d?n, al-‘aql, al-m?l, al-nafs, and al-‘ir? are preserved in cyberspace. The main challenges faced include epistemological, methodological, and practical issues in establishing new technology-based legal rulings. This article recommends integration between Islamic scholars, IT experts, and regulators; the development of a digital fiqh curriculum in Islamic educational institutions; and the formulation of a codified Digital Media Fiqh as a guide to cyber ethics for Muslims.